PRINSIP PROPORSIONAL PERTANGGUNGAN GANTI RUGI DALAM PERKARA WANPRESTASI AKAD MUSYARAKAH (Analisis Putusan Mahkamah Agung RI Nomor 624 K/AG/2017) - Deni Purnama; Asmuni Asmuni; Dhiauddin Tanjung (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This research explores the law consideration used as the foundation of the appearance of the obligation of compensation due to default in the musharakah verdict agreement. In practice, the bias between Islamic and conventional banks often occurs, especially regarding the musharakah agreement, which is sometimes interpreted as a debt agreement, as commonly occurs in traditional banks. Using a normative law research approach, the writer analyzes the internal works of law standards by using decisions of the first level of Religious Courts judges and the cassation level as the object. Based on the analysis, there are two types of law approaches of the judges: formal justice and substantive justice. The judges at the first level of the judiciary used a traditional method by comparing the sound of agreement and the facts of the court. Meanwhile, the substantive justice approach was taken from the cassation level judges who consider not only the agreement's validity but also the agreement's substantial. In this case, the judges on the cassation level managed to explore the substance of equality and partnership principles in the Musharakah agreement. Considering the precautionary principle in the implementation of financing by Islamic banking and the legal relation between the participants of the musharakah agreement, the deficiencies in this agreement will be burdened to each party as the fund deposited proportionally. This research contributes to the conflict resolutions of the Musharakah agreement proportionally